Response to: myositis after SARS-CoV-2 vaccination occurs more frequently than assumed and is probably causally related - H. Quiñones-Moya; A. Camargo-Coronel; M.R. Hernández-Zavala (PAGEPress Publications, 2023)
We thank Finsterer et al. for the attention paid to our publication; we recognize the validity of the points mentioned in their letter to the editor and will try to answer the observations made.